Effect of hydrogen peroxide acetic acid pretreatment on kapok (ceiba pentandra) fruit peel waste for bioethanol production using separated hydrolysis and fermentation methods. (2022) - Budiyono,; Agustiani, Vinalia; Khoiriyah, Lailatul; Hawali Abdul Matin, Hashfi; Rachmawati, Siti
Abstract: The increase in the world's population has an impact on the increasing demand for fuel energy. With the increasing need for fuel, it causes the depletion of fossil fuel sources. For this reason, the search for alternative energy sources for fuel must be developed so that it can be applied for mass use, one of which is bioethanol. Bioethanol is a renewable energy source that has the potential to be developed in Indonesia. Bioethanol is ethanol from the fermentation of sugar, starchpatian or lignocellulosic biomass. This study examines the effect of hydrogen peroxide acetic acid (HPAC) pretreatment of kapok fruit peel waste on the cellulose, hemicellulose, and lignin content produced, examines the effect of fermentation pH on the levels of bioethanol produced, and examines the effect of fermentation time on the levels of bioethanol produced. In the research of bioethanol production, the variables used were pretreatment of raw materials, pH of fermentation (4, 4.5, 5), fermentation time (3, 5, 7 days). The results showed that the pretreatment of HPAC was able to remove 90% of the lignin content in kapok fruit peel waste, while the optimum pH and optimum time for fermentation were obtained at pH 4.5 and day 5 with the content of bioethanol 8.268% and the highest yield of bioethanol is 8.78%.